Validity and Reliability of the Secondary Traumatic Stress Scale—Chinese Version - He, Yi; Liu, Zhiqun; Zhang, Juan; Yao, Jiapei; Xiao, Huan; Wan, Huan (Frontiers in Surgery, 2022)
Objectives: To test the validity and reliability of the Secondary Traumatic Stress Scale - Chinese version in clinical nurses. Methods: According to the translation principles of the Brislin Scale, the original scale was translated, back translated and cross-culturally adapted to form the Chinese version of the Secondary Traumatic Stress Scale. Nurses in three general hospitals in Changsha, Hunan province were surveyed by convenient sampling method from July 2020 to September 2021. Exploratory factor analysis, confirmatory factor analysis, content validity and criterion validity was used to evaluate the validity of the scale. Internal consistency Cronbach's α coefficient, split-half reliability and test-retest reliability were used to evaluate the reliability of the scale. Results: A total of 678 nurses were included in the study. There were 460 people in sample 1 and 218 people in sample 2. Two common factors were extracted by exploratory factor analysis. The cumulative contribution was 65.560%. The two-factor structure model was good (χ2/df=3.137、CFI=0.928、IFI=0.929、GFI=0.842、TLI=0.917、RMSEA=0.099). The I-CVI of the scale was 0.8-1.0. The S-CVI/Ave was 0.94. The Cronbach's alpha coefficient is 0.956. The broken half reliability is 0.920. The retest reliability is 0.910. Conclusion: This study identified two components of the Secondary Traumatic Stress Scale - Chinese version, which has 2 dimensions and 17 items. With good validity and reliability, it is suitable for the assessment of secondary traumatic stress among clinical nurses in the Chinese context.